Avaliação clínica e comparativa da oclusão balanceada bilateral e desoclusão com guia canino sobre a função mastigatória de usuários de prótese total removível - Farias Neto, Arcelino (2009)
The maintenance of masticatory function is especially important for patients who wear complete dentures due to the limitations of this type of prosthesis. Thus, the bilateral balanced occlusion (BBO) is used to achieve, besides other advantages, greater masticatory efficiency. However, analyzing critically the literature, it is observed that there is not enough scientific evidence that support the BBO as the most appropriate occlusal concept in complete dentures. This way, the purpose of the present study was to verify if complete dentures wearers with BBO present better masticatory efficiency and capacity than those with canine guidance (CG). A double-blind controlled crossover clinical trial was conducted. The sample was made of 24 completely edentulous patients. The subjects wore sets of complete dentures with both occlusal concepts for equal periods of 3 months. Objective data were collected through the masticatory efficiency test, performed by the colorimetric method, in which capsules of a synthetic material enclosing fuchsine- containing granules were used. Subjective data were recorded by patient´s ratings of their chewing function, which is the masticatory ability. No significant statistical difference was found for masticatory efficiency (p=0,0952) and masticatory ability (x2=0,5711/ p=0,4498) between the two occlusal concepts studied, as well as there was no correlation between these two variables (p=0,2985). Based on these results, it seems reasonable to use CG for the setup of complete dentures, since it is an easier and quicker technical procedure, until that future researches can come to complement this question